2017
DOI: 10.1002/clc.22689
|View full text |Cite
|
Sign up to set email alerts
|

The role of thyroid hormones in acute coronary syndromes: Prognostic value of alterations in thyroid hormones

Abstract: The prognosis of acute coronary syndromes (ACS) is affected by many factors. Normal thyroid homeostasis is known to alter during various critical illnesses, a condition that has been shown to correlate with the severity of the disease and increased mortality. The purpose of this article is to review literature to emphasize the considerable association of thyroid function with the cardiovascular system and summarize all existing evidence with regard to the role of thyroid hormones alterations during ACS. The el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 42 publications
1
23
0
1
Order By: Relevance
“…The prevalence of LT3S among patients with AMI is 23.3% in this study, which has been reported to be 5-35% in the literature [1,15,16]. The wide range could be attributed to different patient populations.…”
Section: Discussionsupporting
confidence: 46%
“…The prevalence of LT3S among patients with AMI is 23.3% in this study, which has been reported to be 5-35% in the literature [1,15,16]. The wide range could be attributed to different patient populations.…”
Section: Discussionsupporting
confidence: 46%
“…Alteration of thyroid function may adversely affect the heart and cardiovascular system, which has a direct effect on the cardiovascular disease and is caused by a complex relationship with risk factors for the cardiovascular disease . Hyperthyroidism is associated with systolic hypertension, atrial fibrillation, and hypercoagulability, while hypothyroidism can lead to hyperlipidemia and vascular inflammation …”
Section: Introductionmentioning
confidence: 99%
“…The prognosis of acute coronary heart disease is affected by many factors [ 1 ]. Among all neuroendocrine systems, thyroid hormone plays a major homeostatic role in modulating heart rate, cardiac contractility, and arterial peripheral resistance [ 2 , 3 ]. Accumulating evidences show that abnormal thyroid homeostasis is generally associated with increased cardiovascular morbidity and mortality in patients with coronary artery disease (CAD), heart failure, stroke and so on [ 4 9 ].…”
Section: Introductionmentioning
confidence: 99%